2013
DOI: 10.1089/adt.2012.463
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Interference of Drug-Like Molecules with the Respiratory Chain: Toward the Early Identification of Mitochondrial Uncouplers in Lead Finding

Abstract: The electron transport chain (ETC) couples electron transfer between donors and acceptors with proton transport across the inner mitochondrial membrane. The resulting electrochemical proton gradient is used to generate chemical energy in the form of adenosine triphosphate (ATP). Proton transfer is based on the activity of complex I-V proteins in the ETC. The overall electrical activity of these proteins can be measured by proton transfer using Solid Supported Membrane technology. We tested the activity of comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Figure 2C shows that oligomycin A inhibits the hydrolysis of on-column ATP. Further, a series of concentrations of oligomycin A in the mobile phase were run on the MMAC-Muscle column and an IC 50 of 40.2 ± 13.5 nM (Figure 3A) with a maximum reduction of ~60% in ATP hydrolysis was observed, p<0.001, which is consistent with previously reported IC 50 values [20]. While it was clearly demonstrated that hydrolytic activity of F-ATPase/ATP synthase activity was present, a series of concentrations of ADP [1.56 uM to 8 mM] were run on the MMAC-Muscle column to determine whether the ATP synthase activity was also retained.…”
Section: Resultssupporting
confidence: 89%
“…Figure 2C shows that oligomycin A inhibits the hydrolysis of on-column ATP. Further, a series of concentrations of oligomycin A in the mobile phase were run on the MMAC-Muscle column and an IC 50 of 40.2 ± 13.5 nM (Figure 3A) with a maximum reduction of ~60% in ATP hydrolysis was observed, p<0.001, which is consistent with previously reported IC 50 values [20]. While it was clearly demonstrated that hydrolytic activity of F-ATPase/ATP synthase activity was present, a series of concentrations of ADP [1.56 uM to 8 mM] were run on the MMAC-Muscle column to determine whether the ATP synthase activity was also retained.…”
Section: Resultssupporting
confidence: 89%
“…Although targeting the PMF might be expected to be purely mitotoxic, Stock et al (26) have shown that compounds with logP > 6 have generally low mitotoxicity, which is due, they proposed, to low membrane permeability attributable to accumulation in lipophilic membranes.…”
mentioning
confidence: 99%
“…17 However, early generations of SSM-based electrophysiology devices offered only a limited degree of automation and sample output, and thus were not applicable for large-scale profiling purposes. 1820 The current generation of SSM-based devices, the Surfe 2 r 96SE, an automated electrophysiology-based high-throughput instrument, allows simultaneous measurement of up to 96 sensors as well as buffer exchange and optional automated sensor preparation with the pipetting unit, significantly increasing assay performance—a prerequisite for medium- to high-throughput approaches.…”
Section: Introductionmentioning
confidence: 99%